Greater Yam: An overview of its phytochemical profile and potential for ensuring food security - Kalidas Pati; Biswajit Jena; V.B.S. Chauhan; Hanume Gowda; R. Arutselvan; M. Nedunchezhiyan; K. Laxminarayana (JOURNAL OF ROOT CROPS, 2024)
Millions of people in tropical nations rely on cultivated yams (Dioscorea spp.) as their main source of nutrition. Even though these underutilized crops are rich in nutrients, there is a dearth of information on them, which impedes their development and sustainability. Greater yam (D. alata) plant has medical, pharmacological, cosmetic, and industrial uses in addition to its nutritional value. Their bioactive components, which include anti-inflammatory, antibacterial, and antioxidant properties, have recently drawn more interest in scientific investigations. This analysis aims to highlight the undervalued benefits of yams for pharmacological applications and food security. These species differ greatly in their morphology with regard to the length of growing season, the types of tubers produced, the dry matter content of the tubers, and the nutritional and chemical components of the tubers. Nonetheless, there is a dearth of knowledge currently available about yams. As a result, we covered information regarding the botanical description, origin and distribution, genetic resource, agronomy, pharmacological properties, nutritional values, molecular and genomic research, and future prospects regarding yams in this review